Airborne culprits: A comprehensive review of PM, silica, and TCDD in autoimmune diseases - Daniel Galeano-Sánchez; Victoria Morales-González; Diana M. Monsalve; Carolina Ramırez-Santana; Yeny Acosta-Ampudia (Journal of Translational Autoimmunity)
Autoimmune diseases (ADs) are immunological disorders arising from the breakdown of immune tolerance, influenced by various internal and external factors. Persistent exposure to environmental factors, particularly air pollution, is linked to systemic inflammation, oxidative stress, and apoptosis, which contribute to the development of ADs.This review examines the impact of air pollutants, including particulate matter, silica, and TCDD, by analyzing epidemiological studies, animal models, and in vitro assays. It focuses on how air pollution disrupts the immune system, leading to apoptosis, increased oxidative stress, cytokine production, autoantigen release, autoantibody production, and autoreactivity, which are particularly significant in ADs like rheumatoid arthritis, systemic lupus erythematosus, Sjögren's syndrome, and systemic sclerosis. In essence, this approach aims to provide a profound understanding of how exposure to air pollution can initiate or contribute to ADs, offering potential avenues for more targeted preventive and therapeutic strategies.